An Analysis of Directive and Commissive Speech Acts on Two Videos of Collin Abroadcast Channel - Ovika Pretty Precatia; Ch. Evy Tri Widyahening; Luqman Al Hakim (ITScience (Information Technology and Science), 2026)
The research investigated how sellers and buyers used directive and commissive speech acts in English market transactions on YouTube. It also determined the dominant speech act between the two categories. Directive speech acts encouraged the listener to perform specific actions, such as commands or requests. Meanwhile, commissive speech acts bound the speaker to future commitments, including offers or promises. The researcher properly applied a qualitative descriptive analysis method. First, the investigator collected the primary data directly from two bargaining videos on the Collin Abroadcast channel. The researcher observed the transactions carefully and transcribed the spoken interactions. Next, during the data reduction phase, the author sorted the relevant utterances and discarded unnecessary dialogue. Then, the researcher created a structured table to display the linguistic patterns clearly. Finally, the author drew systematic conclusions based on the specific context. The findings systematically revealed some very interesting variations between the two different digital markets. In the Beijing video, the researcher identified exactly 571 total expressions. Directive speech acts appeared slightly more dominant with 286 utterances, driven by initial asks and requests, while commissive acts occurred 285 times. Conversely, in the Cambodia video, the researcher carefully analyzed 395 unique spoken expressions. Here, directive speech acts heavily dominated the conversation with 214 phrases, mostly consisting of various questions, compared to just 181 commissive phrases. Ultimately, the study thoroughly demonstrated how the speech acts functioned dynamically throughout the intense English market transactions on the popular YouTube platform.